Ensino e aprendizagem de ritmos musicais através da oralidade com fala ritmada: uma pesquisa bibliográfica no catálogo de teses e dissertações da CAPES - Côrtes, Felipe Vasconcelos Fontes Rocha (Universidade Federal de São Carlos, 2025)
This dissertation, of a bibliographic nature, investigates the teaching and learning processes of musical rhythms that make use of orality through rhythmic speech. The study begins with a report of an experience that motivated the research question, in which children began to teach each other autonomously, using rhythmic speech as a pedagogical tool. Next, a brief history of music education is presented, with emphasis on the proposals of music educators who use Active Methods, which can include the use of orality in music teaching. The research also examines African and Afro-Brazilian concepts that combine words, orality, spirituality, music, rhythm, body and movement in the teaching and learning processes. The main theoretical references used are Amadou Hampâté Bâ, Kofi Agawu and Gerhard Kubik, whose approaches proved to be predominant among the dissertations and theses analyzed in this research. Regarding the methodology, the investigation is based on content analysis and categorical analysis proposed by Laurence Bardin. To select the academic papers, searches were limited to the CAPES database, using eight descriptors that initially led to 24 papers and, after categorization, six papers were selected for analysis. Based on the quantitative analyses, we observed little production for the 22-year period and a concentration in institutions in the Southeast. With the qualitative analyses of the data collected, it was possible to systematize the recurring concepts in the inventoried research and identify gaps in this field of study. The main concepts analyzed were: Rhythmic Speech; Rhythmic Speech is not alone; Oral/Aural; and Oral Notation. For the concept of Rhythmic Speech, we identified three variations in form and three variations in content. We observed that although many authors make references to these concepts, the signifier often changes but the meaning prevails. Finally, the research concludes by reflecting on the challenges faced, the lessons learned and the main findings of the study. In addition, possible paths for future investigations on the subject are suggested.
Enseñanza y aprendizaje de ritmos musicales a través de la oralidad con habla rítmica: una investigación bibliográfica en el catálogo de tesis y disertaciones de la CAPES
Teaching and learning of musical rhythms through orality with rhythmic speech: a bibliographical investigation in the CAPES theses and dissertations catalog
Keywords: Oralidade; Palavra; Ritmo; Fala ritmada; Percussão; Afro-brasileiro; Orality; Word; Rhythm; Rhythmic speech; Percussion; Afro-Brazilian; LINGUISTICA, LETRAS E ARTES::ARTES::MUSICA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; LINGUISTICA, LETRAS E ARTES::ARTES::MUSICA::CANTO; LINGUISTICA, LETRAS E ARTES::ARTES::MUSICA::INSTRUMENTACAO MUSICAL